Bacterial Infections in Neonates Following Mupirocin-Based MRSA Decolonization: A Multicenter Cohort Study. (5th June 2017) - Pierce, Rebecca; Bryant, Kristina; Elward, Alexis; Lessler, Justin; Milstone, Aaron M.
Abstract : OBJECTIVE: To characterize the risk of infection after MRSA decolonization with intranasal mupirocin. DESIGN: Multicenter, retrospective cohort study. SETTING: Tertiary care neonatal intensive care units (NICUs) from 3 urban hospitals in the United States ranging in size from 45 to 100 beds. METHODS: MRSA-colonized neonates were identified from NICU admissions occurring from January 2007 to December 2014, during which a targeted decolonization strategy was used for MRSA control. In 2 time-to-event analyses, MRSA-colonized neonates were observed from the date of the first MRSA-positive surveillance screen until (1) the first occurrence of novel gram-positive cocci in sterile culture or discharge or (2) the first occurrence of novel gram-negative bacilli in sterile culture or discharge. Mupirocin exposure was treated as time varying. RESULTS: A total of 522 MRSA-colonized neonates were identified from 16, 144 neonates admitted to site NICUs. Of the MRSA-colonized neonates, 384 (74%) received mupirocin. Average time from positive culture to mupirocin treatment was 3.5 days (standard deviation, 7.2 days). The adjusted hazard of gram-positive cocci infection was 64% lower among mupirocin-exposed versus mupirocin-unexposed neonates (hazard ratio, 0.36; 95% confidence interval [CI], 0.17–0.76), whereas the adjusted hazard ratio of gram-negative bacilli infection comparing mupirocin-exposed and -unexposed neonates was 1.05 (95% CI, 0.42–2.62). CONCLUSIONS: In this multicentered cohort of MRSA-colonized neonates, mupirocin-based decolonization treatment appeared to decrease the risk of infection with select gram-positive organisms as intended, and the treatment was not significantly associated with risk of subsequent infections with organisms not covered by mupirocin's spectrum of activity. Infect Control Hosp Epidemiol 2017;38:930–936